The Peculiarities of Crises Management in Schools - Balsevičienė, Birutė; Šinkariova, Liuda (Pedagogika, 2013)
Critical incidents are sudden, unexpected, often life-threatening time-limited events that may overwhelm an individual’s capacity to respond adaptively. Crises are sudden, unexpected events that have an “emergency quality” and have the potential to impact on the entire school community. In schools, a crisis might be considered as any situation faced by staff or students causing them to experience unusually strong emotional reactions that may interfere with their ability to perform. Authors review the research in school crises management in foreign countries, especially in the USA and other western countries and the situation in this field in Lithuania. There authors describe the definitions of crises and analyze models of crises management in schools. The main object of this research is management of crises in schools and its models. The purpose of this article is to review and summarize the researches in foreign countries and in Lithuania and outline the main directions for the future researches in this field. The main goals of this article were to disclose the conception of crises in school, to review the research in school crises management in foreign countries and Lithuania, to review practical activities in Lithuania. The method of this research was the analysis of scientific literature in Lithuania and foreign countries. The research results and their analysis let draw the following conclusions: The conception of crises in school is multiple, but there are three main features: incidents are unexpected and sudden, have the potential to impact on the part or entire school community and interfere with their ability to perform. The most common model of crises management is PPRR model (prevention, preparation, response, recovery model) in schools. In Lithuania there is the law of crises management in schools, pedagogical psychological services crises management teams were instructed in main crises management principals, schools crises management teams are instructed in these principals, too.